Timed Behavioral Specification in Globally Asynchronous Locally Synchronous systems - Yu Tonglan; Liu Jie; Zhang Juan; Wu Qujing (Institute of Advanced Engineering and Science, 2013)
In this paper, we propose a PolGALS language for safety critical GALS(Globally Asynchronous Locally Synchronous) systems. The formal syntax and semantics are given and its compilation and implementation are defined. The language is based on timed CSP(communicating sequential process) style rendezvous between clock domains, aiming at modelling the timed behavioral of safety critical GALS systems. PolGALS is used to design timed behavioral pattern to implement timing requirements, e.g. delay, timeout, deadline, timed interrupt,etc. PolGALS provides a mechanism for implementation of timed behavioral pattern and potential for their formal verification because it is based on a PolGALS model of computation and its formal semantics. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3257